Advice for salt, sugar and fat intake habits among adults: a national-based study - Suele Manjourany Silva; Luiz Augusto Facchini; Elaine Tomasi; Roberto Piccini; Elaine Thumé; Denise Silva da Silveira; Fernando Vinholes Siqueira; Alitéia Santiago Dilélio; Bruno Pereira Nunes; Mirelle de Oliveira Saes (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2013)
INTRODUCTION : A healthy diet is recognized as an important strategy for promoting health as an essential part of non-pharmacological therapy of various health problems. OBJECTIVE : To analyze the reported advice for the intake of salt, sugar and fat for the Brazilian adults living in urban areas. METHODOLOGY : National-based cross-sectional study with 12,402 adults interviewed in 100 Brazilian cities. RESULTS : The most prevalent advice was to low fat intake (38%), followed by the advice to low salt and sugar intake (36%) and sugar (29%). The percentage of receiving different advice was similar and more common among women, older people, those with a partner, higher economic class, former smokers, active and in person with physician diagnoses of hypertension, diabetes and overweight. People with white skin color received more advice to eat healthy food, except for the orientation to low salt intake. CONCLUSION : The results show a low prevalence of advice, which configures a missed opportunity to prevent health problems. Although dietary counseling should not be understood only as the transmission of advice regarding some nutrients, it is important to develop actions in order to qualify services and health professionals, allowing the population to have access to qualified information about the benefits of having healthy lifestyles.